Energy drinks and other dietary supplement use among adolescents attending secondary schools in Trinidad and Tobago. Issue 10 (7th January 2014) - Babwah, Terence J; Maharaj, Rohan G; Nunes, Paula
Abstract Objective The objective of the present study was to determine the knowledge and practices among Trinidad and Tobago school-attending adolescents towards energy drinks (ED), alcohol combined with energy drinks (AwED), weight-altering supplements (WAS) and vitamin/mineral supplements (VMS) and their experience of adverse effects associated with such use. Design A cross-sectional, proportionate, stratified sampling strategy was adopted using a self-administered, de novo questionnaire. Setting Secondary schools throughout Trinidad and Tobago. Subjects Students aged 15–19 years. Results Five hundred and sixty-one students participated, an 84 % response rate; 43·0 % were male, 40·5 % East Indian and 34·1 % mixed race. VMS, ED, WAS and anabolic steroids were used by 52·4 %, 44·0 %, 8·9 % and 1·4 % of students, respectively, with 51·6 % of ED users using AwED. Predictors of use of AwED were males and students who played sport for their school (OR = 1·9; 95 % CI 1·2, 3·2 and OR = 2·6; 95 % CI 1·4, 4·7, respectively). Predictors of ED use were males and attendees of government secondary schools (OR = 1·7; 95 % CI 1·1, 2·4 and OR = 1·7; 95 % CI 1·2, 2·4, respectively). Side-effects, mainly palpitations, headaches and sleep disturbances, were reported in 20·7 % of dietary supplement users. Conclusions Many adolescent students in Trinidad and Tobago use dietary supplements, including ED and AwED, and about one-fifth of users experience side-effects. Identification of students at risk for ED, AwED and WAS use and education of students about the dangers of using dietary supplements need to be instituted to prevent potential adverse events.